Pertanggungjawaban Notaris Terhadap Pemalsuan Kepemilikan Saham dalam Akta Otentik - Clavelda Sheryl Wiweldy (LPPM Universitas Ekasakti Padang, 2023)
A notary, holding a dual role as a professional and a public official, plays a crucial preventive role in averting legal complications through the creation of authentic deeds, serving as conclusive evidence. As stipulated by Law Number 30 of 2004 on Notary Positions, notaries are obligated to justify the deeds they produce. This study aims to examine the comprehension regarding the regulation of the responsibilities of notaries found in violation of their duties and to ensure legal protection for parties affected by the notary's data falsification. The research outcomes indicate that, as a legal consequence, notarial deeds can be subject to annulment, and based on legally binding decisions, the implicated notary can face administrative, civil, and criminal accountability.